Mini Review : Sedem System as a Tool to Characterize Excipients in Solid Dosage Form - Iyan Sopyan; Rizka Guntina Khairunisa (Universitas Padjadjaran (Unpad), 2021)
SeDem System is a new system that can be applied in solid dosage form preformulation studies of medicines. It have parameters to evaluates critical quality attributes of materials that have an impact on final drug product’s quality. SeDeM studies could be used as a method for identifying the best excipient and calculating the maximum amount of excipient required for formulation. SeDeM method can , providing formulation with the lowest amount of excipients as it combines the Active Pharmaceutical Ingredients (API) with only one excipient and the standard formula of lubricants, thus avoiding the used of unnecessary excipients, such as diluents, binders and agglutinants. The information given by the SeDeM system contributes to a quality by drug design development.Keywords: SeDeM System, Excipients